Administrators' Perception of Leadership Tenure on Goal Attainment at Nigerian Federal Universities - Ayobami Abimbola Oyedeji (Journal of General Education and Humanities, 2025)
University goal attainment (GA) is the extent to which universities achieve their vision through teaching, research, and community services (CSs). However, the literature shows that the GA is diminishing in Federal Universities (FUs) in Nigeria, particularly in the southwest. Previous studies on GA have emphasized leadership and participatory management practices more than the leadership tenure (LT) factor. Therefore, this study was designed to examine administrators' perceptions of the influence of LTs on GAs in FUs in southwestern Nigeria. The survey research design of the expost-facto type was adopted for this study. Qualitative data were collected through the Key Informant Interview (KII). The sample size for this study comprised three deans and 37 Heads of Departments (HoDs) from the University of Ibadan, Ibadan, Obafemi Awolowo University, Ile-Ife, and the University of Lagos, Akoka. Content analysis was used to analyze information obtained from heads of departments and deans across three FUs selected for the study. The HoDs and Deans exhibited a democratic leadership style, whereas the LT factor varied from two to four years across the universities. The LTs, though sacrosanct, varied across the universities. The leadership time frame, experience, and style were potent variables in the GA of FUs in southwestern Nigeria. Leadership experience, style, and LT should be improved for effective university service delivery.